THE EFFECTIVENESS OF APPLIED EXERCISE ACCORDING TO FOLK WISDOM TO ENHANCE THE PHYSICAL FITNESS OF THE ELDERLY IN KHAO SAMOR KHON SUBDISTRICT THA WUNG DISTRICT LOPBURI PROVINCE - Sriya , Kathavut; Yingdamnun, Pattarapong (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) to study the effectiveness of applied exercise according to folk wisdom to enhance the physical fitness of elders and 2) to compare the components of physical fitness after applied exercise according to folk knowledge between the experiment group and the control group. The method was a quasi - experimental research design with healthy elderly subjects living in Khao Samor Khon Subdistrict, Tha Wung District, Lopburi Province. The subject groups were purposive sampling. In addition, the selection was a simple random sampling method. There were divided into two groups: the experimental group (15 = n) and the control group (15 = n). The data from the Physical fitness test were collected pretest and posttest for 12 weeks. The statistical values were mean, standard deviation, and independent t - test analysis, etc. Research instruments include A manual for physical fitness tests and standards for people aged 60 - 69 years and A manual for applied exercise activities based on folk wisdom to enhance the physical fitness of the elderly. The research results found that the study to compare averages includes: The Back Scratch of the right hand on top, The 30 Seconds Chair Stand, the Agility Course, and the 2 Minutes Step Up and Down. After applying exercise according to folk wisdom between the experiment group and the control group. A statistically significant difference (p < 0.05). In conclusion, applied exercise according to folk wisdom. Greatly increases the physical fitness level of the elderly very well.